The Effect of Geogebra-Assisted Problem-Based Learning and Motivation on Mathematics Learning Outcomes of SMA Hang Tuah 5 Sidoarjo Students - Lilik Handayani; Mustaji Mustaji; Harwanto Harwanto (Journal of Educational Sciences, 2026)
The development of digital technology encourages the application of innovative learning models to improve students' mathematics learning outcomes. This study aims to analyze the influence of GeoGebra-assisted Problem-Based Learning (PBLGG), learning motivation, and the interaction of the two on students' mathematics learning outcomes. The study used a quantitative approach with quasi-experimental methods and a non-equivalent control group pretest-posttest design. The research sample consisted of 72 students of Phase E of SMA Hang Tuah 5 Sidoarjo which were divided into experimental classes and control classes. Data was collected through mathematics learning outcome tests and learning motivation questionnaires, then analyzed using the Independent Sample t-test and two-way ANAVA (Two-Way ANOVA). The results showed that there was a difference in mathematics learning outcomes between students who took part in PBLGG and students who participated in Problem-Based Learning (PBL) without the help of GeoGebra. Learning motivation also affects mathematics learning outcomes. There is an interaction between learning model and learning motivation on students' mathematics learning outcomes. These findings show that the integration of PBL, GeoGebra, and learning motivation is an effective learning strategy to improve mathematics learning outcomes and support more active, meaningful, and student-centered learning.